Lamina Cribrosa Thickness in Patients with Branch Retinal Vein Occlusion: A Cross Sectional Comparative Evaluation Using Enhanced Depth Imaging Optical Coherence Tomography - Bhardwaj, Rahul; Dhawan, Aeshvarya; Vats, Vatsala; Gupta, Priyanka; Singh, Anupam; Tomar, Nidhi (International Journal of Advanced Medical and Health Research, 2024)
Abstract Background: Retinal vein occlusion (RVO) is one of the most common causes of retinal vascular disease, second to diabetic retinopathy. We aimed to compare the lamina cribrosa thickness (LCT) of patients with unilateral branch RVO (BRVO) versus healthy individuals. Materials and Methods: This was a hospital-based, prospective, cross-sectional, and comparative study. Participants were newly diagnosed RVO cases (n = 25) and apparently normal age-matched healthy controls (n = 25). All the participants underwent systemic and comprehensive ophthalmic examination, including refraction and enhanced depth imaging optical coherence tomography. Relevant parameters were compared between the groups using the independent t-test. Statistical significance thresholds were set at a P < 0.05. Results: The mean age of cases (66.7% female) and controls (52% female) was 55.9 ± 7.4 and 59.4 ± 7.0 years, respectively, (P = 0.089). The mean LCT of the affected eyes in cases (176.6 ± 28.3 μm) was significantly lower compared to the unaffected eyes of cases (200.6 ± 33.1 μm, P = 0.008) and control eye (230.9 ± 36.9 μm, P = 0.001). Conclusions: A thinner lamina cribrosa (LC) was observed in both eyes of unilateral RVO patients compared with healthy, nonglaucomatous subjects' eyes. The role of LCT as a local mechanical factor in the pathogenesis of BRVO and their relationship to systemic factors merits further investigation.